PENGEMBANGAN MODEL PEMBELAJARAN TF-P5M PADA PROGRAM STUDI TATA BUSANA - Wahyu Eka Priana Sukmawaty; Sri Purwani (Institut Agama Islam Negeri (IAIN) Bone, 2020)
The concept of teaching factory is a learning process that teaches vocational high school students about all the processes in a company (factory), including soft skills and hard skills. There needs to be the development of the teaching factory learning model in accordance with the competency of the Fashion Study Program. This research used Research and Development (RD) methods. Data collection was done at SMKN 6 Yogyakarta. The stages in this study were stage (1) To Review The Relevant Literature and the Plan The Objectives stage can be used as one; (2) Develop Preliminary Model Stage; and (3) Preliminary Field Testing stages are validated, hypothetical models. The source of the data is the manager of the teaching factory SMKN 6 Yogyakarta Fashion Study Program. For validation of learning models that have been developed that is done by expert judgment who is an expert in the field of teaching factory. The results of this study obtained TF-P5M learning model composed of: (1) Determination of competencies that will be achieved by analyzing the Competency Standards of Graduates (SKL) subjects and analysis of the development of the industry towards fashion all of these things are included in the learning implementation plan; (2) Determination of the allocation of lesson time, facilities and infrastructure; (3) Division of student groups with a maximum of 5 members; (4) Production of products/services is carried out in groups; (5) Marketing via E-commerce; and (6) Evaluate the products and marketing processes carried out by teachers.Keywords: teaching factory, learning model, fashion study program